DESCRIPTIVE ANALYSIS OF EMPLOYEE SATISFACTION OF ASTRA INFRA PORT EASTKAL USING THE LIKERT SCALE APPROACH - Herliansyah Herliansyah; Dedy Darmawan (Jurnal Mahasiswa Manajemen, 2026)
Employee performance in the port sector is greatly influenced by psychological aspects such as job satisfaction. This descriptive study maps these conditions at Astra Infra Port Eastkal using Maslow's Theory and the Likert Scale. Through a quantitative approach, a 15-item questionnaire was distributed to 100 permanent employees using a saturated sampling technique. The results of the research show that the general satisfaction index is in the high category (3.65). Among all variables, security assurance was the most prominent aspect with a value of 3.73, while physiological needs were stagnant in the most distended position (3.55). The critical point of this research is in the indicator of salary suitability and workload which is only stuck at 3.43 (sufficient category), even to the point of triggering a negative response from 21% of employees. This condition is proportional to the work award points (3.80) and the provision of PPE/safety (3.79) which successfully occupies the top two rankings. On a macro level, this non-monetary climate has proven to be effective in reducing workers' disappointment related to financial affairs. As a corrective step, management needs to overhaul the wage system for contract workers whose portion dominates the human resource structure (57%), without relaxing safety standards and a culture of appreciation that has proven to be solid